Dog-Walking as a Catalyst for Physical Activity: Mitigating the Risk of Sarcopenia and Frailty in Older Adults - Czarny, Norbert; Śmigielski, Michał; Figwer, Agnieszka; Dzitkowska, Kinga; Broniecka, Anna; Garbaciak, Jędrzej; Figwer, Krzysztof; Kasterka, Natalia; Karbownik, Liwia; Kolasa, Magdalena (Quality in Sport, 2026)
Background: Sarcopenia and frailty are prevalent geriatric syndromes associated with falls, disability, hospitalization, institutionalization and mortality. Physical inactivity is a modifiable contributor to both conditions. Dog walking has been proposed as a pragmatic, socially embedded and potentially adherence-enhancing form of habitual physical activity in later life. Objective: To critically evaluate whether dog walking can act as a catalyst for physical activity and thereby mitigate risk factors for sarcopenia and frailty in older adults. Methods: A structured narrative review was prepared using PubMed/MEDLINE-indexed articles, PubMed Central records, journal publisher pages, WHO guidance, geriatric consensus statements, systematic reviews, network meta-analyses, cohort studies and injury-epidemiology studies. Evidence was organized into five domains: dog walking and physical activity; dog walking and mobility, falls and fear of falling; pet ownership and frailty; exercise interventions for sarcopenia and frailty; and dog-walking-related injuries. Certainty was summarized using a GRADE-informed approach. Results: The strongest direct evidence indicates that dog ownership and dog walking are associated with higher physical activity, higher daily step counts and greater likelihood of meeting physical activity recommendations. However, direct evidence that dog walking prevents sarcopenia or reverses frailty is limited and largely observational. Guidelines and randomized-trial syntheses support resistance and multicomponent exercise as core interventions for sarcopenia and frailty-related outcomes. Dog walking is therefore best interpreted as an adherence-enhancing behavioral adjunct rather than a primary anti-sarcopenia intervention. Injury studies also identify clinically relevant risks, including fractures, falls and leash-related upper-limb trauma.